2017
DOI: 10.7554/elife.30212
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of incubation periods

Abstract: The incubation period for typhoid, polio, measles, leukemia and many other diseases follows a right-skewed, approximately lognormal distribution. Although this pattern was discovered more than sixty years ago, it remains an open question to explain its ubiquity. Here, we propose an explanation based on evolutionary dynamics on graphs. For simple models of a mutant or pathogen invading a network-structured population of healthy cells, we show that skewed distributions of incubation periods emerge for a wide ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 31 publications
7
38
0
Order By: Relevance
“…2), even though we used a single pathogen strain to infect a single host variety. This observation is consistent with recent modelling of distributions of incubation periods (Ottino-Loffler et al, 2017), but it contradicts the established view in the literature 430 on Z. tritici according to which lesions appear after an asymptomatic period of approximately two weeks (Kema et al, 1996;Steinberg, 2015). Shaw (1990) used pycnidiospores from the natural field population of Z. tritici to inoculate wheat plants in the greenhouse and found that lesions were appearing continuously during the period of up to 25-30 days.…”
Section: Discussionsupporting
confidence: 83%
“…2), even though we used a single pathogen strain to infect a single host variety. This observation is consistent with recent modelling of distributions of incubation periods (Ottino-Loffler et al, 2017), but it contradicts the established view in the literature 430 on Z. tritici according to which lesions appear after an asymptomatic period of approximately two weeks (Kema et al, 1996;Steinberg, 2015). Shaw (1990) used pycnidiospores from the natural field population of Z. tritici to inoculate wheat plants in the greenhouse and found that lesions were appearing continuously during the period of up to 25-30 days.…”
Section: Discussionsupporting
confidence: 83%
“…Over the last hundred years, researchers accumulated a lot of data on incubation periods for various diseases in various populations. These data and the existing literature on the subject are thoroughly discussed in [BOL17], a recent paper that motivated the present study, so we are only giving a brief overview of the most imporant features of the data, referring to [BOL17] and references therein for further details.…”
Section: Introductionmentioning
confidence: 99%
“…All of these data show that within the same population group, a simultaneous exposure to the same pathogen does not result in simultaneous development of symptoms in all individuals belonging to the group. Instead, Figure 1: Data redrawn from historic examples (reproduced from [BOL17], with the authors' permission). Dashed red curves are lognormal densities and solid blue curves are Gumbel densities predicted in [BOL17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations